Long-chain polyunsaturated fatty acids in plasma and erythrocyte membrane lipids of children with phenylketonuria after controlled linoleic acid intake - Pöge, Andreas; Bäumann, K.; Müller, E.; Leichsenring, Michael; Schmidt, Hildgund; Bremer, Hans J. (Journal of inherited metabolic disease, 1998)
It has been reported that children with classical phenylketonuria (PKU) have reduced levels of arachidonic acid (AA, 20:4 n-6) and docosahexaenoic acid (DHA, 22:6 n-3) in plasma and membrane phospholipids compared to controls and may therefore require supplementation. However, it is not established that these changes are specific for PKU. They may as well be attributed to the specific composition of a largely vegetarian diet used for dietary PKU treatment. We therefore investigated the fatty acid composition of plasma phospholipids (PL), plasma cholesterol esters (CE), red blood cell phosphatidylcholine (PC), and red blood cell phosphatidylethanolamine (PE) in two groups of PKU patients including 8 children between 1 and 6 years (group A), 9 adolescents between 11 and 18 years (group B), and 20 age-matched healthy controls. Group A had good dietary control (median plasma phenylalanine 272 μmol/L during the last 6 months before phospholipid analysis) while median phenylalanine in group B was 714 μmol/L (p<0.001). When compared to age-matched controls, group A showed significantly lower DHA levels in PE (4.21 vs 5.85 weight% (wt%), p<0.01), in PC (1.02 vs 1.25 wt%, p<0.05) and in CE (0.25 vs 0.54 wt%, p<0.05). There was no significant difference of DHA between group B and controls. AA levels were similar in phospholipids of all groups. We conclude that reduced levels of long-chain polyunsaturated fatty acids in PKU patients occur only in those patients with strict dietary therapy with respect to n-3 fatty acids, most probably caused by reduced intake of n-3 fatty acids.
Online veröffentlicht: 1. Juni 1998
Gesehen am 19.06.2024